Two new species of the genus Derisemias Jordan (Coleoptera, Anthribidae) from Japan and Taiwan - Imada, Shunsuke (Zootaxa, 2019)
Derisemias tsutsumiuchii sp. nov. and Derisemias kojimai sp. nov. are described from Japan and Taiwan, respectively. These new species are easily distinguished from the known species by positions and sizes of tufts on elytral disc and color pattern of body surface.